Effect of Integrated Psychobehavioral Care on Emotional-Behavioral Responses, Cognitive Changes in Outpatients with Schizophrenia Followed Up: Based on a Prospective Randomized Controlled Study. (16th June 2022) - Yao, Yao; Xu, Yali; Guo, Hongyan; Han, Kunxiu; Dai, Zhuo
Abstract : Background. In recent years, influenced by the continuous improvement and development of the medical service model and the increasing demands of modern people for the quality of clinical care, the clinical treatment of schizophrenic groups has also received widespread attention and importance from all sectors of society. Psychobehavioral care is administered to patients during active antipsychotic treatment, which can maximize the patient's cooperation with clinical work and thus play an auxiliary role in treatment. Aims. To investigate the impact of emotional-behavioral responses, cognitive changes in outpatient follow-up of schizophrenic patients with integrated psychobehavioral care. Materials and Methods. One hundred cases of schizophrenia patients with outpatient follow-up in our hospital from March 2017 to March 2019 were selected as prospective study subjects and divided into a comparison group and an observation group of 50 cases each according to a random number table. Among them, the comparison group implemented conventional psychobehavioral care, and the observation group implemented integrated psychobehavioral care. The differences in compliance behavior, negative emotions, cognitive behavioral changes, and pain scores before and after care of schizophrenia patients in the outpatient follow-up were compared between the two groups. Results. After care, the compliance behavior, negative emotions, cognitive behavioral changes, and pain scores of schizophrenia patients in both groups with outpatient follow-up were significantly improved and significantly higher in the observation group than in the comparison group, and statistics showed that this difference was statistically significant (P < 0.05 ). Conclusion. Integrated psychobehavioral care combined with conventional psychobehavioral care can effectively enhance the compliance behavior of outpatient follow-up schizophrenia patients, improve the negative emotions and pain of patients, and facilitate the active treatment of patients to improve their prognosis. It has some reference value for outpatient follow-up schizophrenia patient care.